Acoustic impedance and electromechanical coupling coefficient of 2-2 parallel connectivity barium titanate piezoelectric ceramic-Portland cement composites - Rattiyakorn Rianyoi (2018)
© 2016 Taylor & Francis Group, LLC. In this paper, the 2-2 parallel connectivity barium titanate (BT) piezoelectric ceramics and Portland cement (PC) were fabricated by dice-and-fill method. The acoustic impedance (Zc) and electromechanical coupling coefficient (Kt) of composites were experimentally investigated as a function of BT ceramic content. When BT ceramic content increases from 30 to 70 vol%, Zcvalues increases from 8.51 to 14.32 kg⋅m−2s−1. According to the results, the composites with BT ceramic content of 30 to 50 vol% showed Zcvalues matching with concrete materials. In addition, with the optimum BT ceramic content of 30 to 50 vol% where the Ktvalues of composites were 17.31 to 19.59%. These composites therefore have promising characteristics for potential use as smart materials for structural health monitoring applications in concrete structures.